CULTIVATING CULTURAL SYNERGY: UNIFYING BOARDING SCHOOLS, LOCAL WISDOM, AND AUTHENTIC ISLAMIC VALUES FOR THE ENHANCEMENT OF ISLAMIC IDENTITY - Fatahillah, Auliya’; Chuanchen, Chuanchen; Zaini, Abdul Wahid (Managere: Indonesian Journal of Educational Management, 2023)
The aim of this research is to determine the form of integration of Islamic boarding school efforts with local wisdom and Islamic values authentically in strengthening Islamic identity in a global context. This research uses a qualitative approach with a case study type. Data was collected from observation, interviews, and documentation. Key informants in this research included one of the caregivers, the head of the Islamic boarding school, and the Tarbiyatul Islamiyah Foundation Islamic Boarding School Education Bureau. Data is analyzed through data condensation, data presentation, and concluding. Source triangulation techniques were used to obtain valid and relevant data. One form of integration of Tarbiyatul Islamiyah Foundation Islamic boarding school education with local wisdom and authentic Islamic values , which are still strong today as an act of strengthening Islamic identity in globalization is (1) Integration of the bandongan method and (2) sorogan method into book literacy culture. Yellow as well as Qur'an literacy culture. Islamic boarding school activities are an acculturation activity of the teachings of Islamic civilization and the local culture of the Indonesian people.